Association of the Monocyte–to–High-Density Lipoprotein Cholesterol Ratio With Diabetic Retinopathy - Tang, Xixiang; Tan, Ying; Yang, Yi; Li, Mei; He, Xuemin; Lu, Yan; Shi, Guojun; Zhu, Yanhua; Nie, Yuanpeng; Li, Haicheng; Mu, Panwei; Chen, Yanming (Frontiers in Cardiovascular Medicine, 2021)
Background: Chronic inflammation in type 2 diabetes mellitus (T2DM) is an essential contributor to the development of diabetic retinopathy (DR). The monocyte–to–high-density lipoprotein cholesterol (HDL-C) ratio (MHR) is a novel and simple measure related to inflammatory and oxidative stress status. However, little is known regarding the role of the MHR in evaluating the development of DR. Methods: A total of 771 patients with T2DM and 607 healthy controls were enrolled in this cross-sectional study. MHR determination and eye examination were performed. The association of MHR with the prevalence of DR in T2DM patients was analyzed. Results: The MHR in patients with DR was significantly higher than that in both non-DR diabetic patients (P < 0.05) and healthy controls (P < 0.01). No significance was observed in the MHR of different DR severity grades. Moreover, the MHR was similar between patients with non-macular oedema and those with macular oedema. Logistic regression analysis demonstrated that MHR was independently associated with the prevalence of DR in diabetic patients [odds ratio (OR) = 1.438, 95% confidence interval (CI): 1.249–1.655, P < 0.01]. After additional stratification by HbA1c level and diabetic duration, the MHR was still independently associated with the prevalence of DR. Conclusions: Our study suggests that the MHR can be used as a marker to indicate the prevalence of DR in patients with T2DM.